ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REALISASI PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SAMBAS - Andresti, Opie; Jaurino (Jurnal Akuntansi, Auditing dan Investasi, 2023)
Regional Native Income is one of the indicators of the independence of a region's autonomy in an effort toexplore potential and increase revenue sources. This study aims to analyze what factors affect RegionalNative Income. The factors analyzed are GRDP, Total Population and Number of Industries from 2012-2021in Sambas Regency.This study used the Saturated Sampling (Census) method. The sample used is data onreports on the receipt of Regional Original Income, GRDP, Number of Population and Number of Industriesper year for the 2012-2021 period obtained from the Central Statistics Agency. Data analysis using multiplelinear regression, with the help of the IBM SPSS Statistics 24 software program.The results showed that theGRDP variable had a significant effect on Regional Original Income, The Number of Population and Numberof Industries did not affect Regional Original Income. Meanwhile, simultaneously the variables of GRDP,Number of Population and Number of industries have a significant effect on the Original Income of theSambas Regency